Risk Factors for Residual Vitreous Cortex at the Fovea after Posterior Vitreous Detachment during Vitrectomy in Ocular Trauma - Anan Wang; Zhenquan Zhao; Qihua Xu; Yaohua Wang; Hongfei Liao (Journal of Ophthalmology)
Purpose. To investigate the frequency and patterns of the residual vitreous cortex (RVC) at the fovea after posterior vitreous detachment (PVD) during vitrectomy after ocular trauma and the risk factors associated with its occurrence. Methods. A cross-sectional, multicenter, and observational study was conducted in 72 consecutive patients who underwent pars plana vitrectomy after ocular trauma. In patients with PVD after vitrectomy, RVC patterns were visualized using triamcinolone acetonide staining and were classified as diffuse or focal. A multivariate logistic regression analysis was performed to evaluate the association between RVC and various factors, such as the patient’s age, preoperative visual acuity, days after injury, the existence of spontaneous PVD, and the type of injury prior to vitrectomy. Results. Of the 72 eyes with trauma, 35 eyes (48.6%) showed RVC on the macula, of which 19 (54.3%) were of the diffuse type and 16 (45.7%) were of the focal type. A multivariate logistic regression analysis showed that age (OR = 0.933, P=0.025) and days after injury (OR = 0.862, P=0.013) had a significant impact on RVC. Conclusions. RVC at the fovea is very common after spontaneous or surgical PVD during vitrectomy. Younger patients are more likely to show RVC if vitrectomy is performed soon after injury.